Low-Carbon Sustainable Precincts: An Australian Perspective - Bunning, Jessica; Beattie, Colin; Rauland, Vanessa; Newman, Peter (Adver, SUSTDE, 2013)
Australia’s urban built environment contributes significantly to the nation’s greenhouse gas emissions; therefore, encouraging urban development to pursue low-carbon outcomes will aid in reducing carbon in the overall economy. Cities and urban areas are configured in precincts, which have been identified as an ideal scale for low-carbon technologies that address energy, water and waste. Even though new governance models and systems are being created to enable low-carbon precincts to operate with a degree of independence within a broader centralised utility structure, greater effort is required to refocus governance on this smaller scale of delivery. Furthermore, at this time, no consistent carbon accounting framework is in place to measure emissions or emission reductions at this scale, thereby limiting the ability to acknowledge or reward progressive, sustainable low-carbon developments. To respond to this situation, a framework is proposed that could form both the basis of a carbon certification scheme for the built environment and provide a platform for generating carbon credits from urban development.